Dramaturgi Kehidupan Pengemis Alun-Alun Kabupaten Jember (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Poverty is a limitation for marginalized communities to join the world of work and is made more difficult by the complexity of company job qualifications (educational diplomas). High levels of economic need and few job opportunities make it difficult to survive, so being unemployed becomes something to do. In an effort to survive, tight conditions narrowed the mind's visibility so that all roads would be taken, resulting in the phenomenon of beggars spreading across the Jember city square. This research uses a phenomenological approach by understanding the phenomenon of begging which is discussed from the perspective of the perpetrator, which aims to reveal the real life of beggars in Alun-alun, Jember district. This research takes the perspective of Erfing Goffman's dramaturgical theory which views life as a stage for drama. The beggar label is not always about poverty. Some individuals use the "job" of begging as a way to be lazy about working, even though their qualifications are capable. In this research, the conclusion was drawn that the beggars in Jember Square are not all poor people with limitations in working, there are still people who are able to sell their self-worth by becoming beggars under the pretext of a more promising income. Apart from that, there are no effective efforts from Satpol PP to follow up on the phenomenon of begging. Therefore, the role of the Jember Regency government is needed so that it can implement appropriate legal policies related to the phenomenon of begging and the lack of job opportunities.